2014
DOI: 10.18632/oncotarget.2413
|View full text |Cite
|
Sign up to set email alerts
|

FOXF1 mediates mesenchymal stem cell fusion-induced reprogramming of lung cancer cells

Abstract: Several reports suggest that malignant cells generate phenotypic diversity through fusion with various types of stromal cells within the tumor microenvironment. Mesenchymal stem cell (MSC) is one of the critical components in the tumor microenvironment and a promising fusogenic candidate, but the underlying functions of MSC fusion with malignant cell have not been fully examined. Here, we demonstrate that MSCs fuse spontaneously with lung cancer cells, and the latter is reprogrammed to slow growth and stem-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 60 publications
2
64
0
Order By: Relevance
“…Table 4). Identification of negative association between FOXF1 and RB/E2F signalling (26) and positive association with epithelial-mesenchymal transition confirmed previous reports (27), but the potential relationship between high FOXF1 and inhibition of mTOR signalling is novel and has not been shown previously.…”
Section: Foxf1 Expression Levels Are Inversely Correlated With Mtor Ssupporting
confidence: 88%
“…Table 4). Identification of negative association between FOXF1 and RB/E2F signalling (26) and positive association with epithelial-mesenchymal transition confirmed previous reports (27), but the potential relationship between high FOXF1 and inhibition of mTOR signalling is novel and has not been shown previously.…”
Section: Foxf1 Expression Levels Are Inversely Correlated With Mtor Ssupporting
confidence: 88%
“…This phenomenon is a more efficient mechanism of DNA-exchange and cellular reprogramming than the accumulation of mutations in single cells (Bastida-Ruiz et al 2016; Dittmar et al 2013; Duelli and Lazebnik 2003). Growing in vitro (Busund et al 2002, 2003; Shabo et al 2015; Wei et al 2014), in vivo (Powell et al 2011; Silk et al 2013), and clinical (LaBerge et al 2017; Lazova et al 2013; Yilmaz et al 2005) data indicate that this process occurs in solid tumors and may play a significant role in clinical tumor progression. Moreover, this process generates malignant cell clones (hybrids) with reduced susceptibility to oncological treatments (Carloni et al 2013; Nagler et al 2011; Wang et al 2012; Yang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The artificial fusion of UC-MSCs with esophageal cancer cell line EC9706 resulted in hybrids with decreased cell growth, increased apoptosis and suppressed tumorigenicity 31. UC-MSCs can spontaneously fuse with lung cancer cell line H441 to form synkaryonic hybrids and reprogram the transcriptome of the lung cancer cells through FOXF1, which reduces their growth rate and tumorigenicity 62. Another study showed that UC-MSCs can exchange membrane proteins and fuse with several tumor cell lines (breast carcinoma cell line MCF-7; Ovarian cancer cell lines NIH OVCAR-3 and SK-OV-3) and enhance the cancers' cell growth.…”
Section: The Mechanism Of Mscs In Anticancer Therapiesmentioning
confidence: 99%